Early discontinuation of immune checkpoint inhibitor therapy prior to disease progression in patients with metastatic non-small cell lung cancer: a survival analysis - McKinley, Blake J.; Pai, Tanmayi S.; Wolf, Emily B.; Li, Shenduo; Correia, Guilherme Sacchi de Camargo; Zhao, Yujie; Manochakian, Rami; Lou, Yanyan (Frontiers in Oncology, 2024)
Introduction Limited survival data are available for patients with metastatic non-small cell lung cancer (mNSCLC) who stop immune checkpoint inhibitor therapy (ICI) early for reasons other than progression of disease (POD), such as immune-related adverse events (irAEs). Methods We conducted a retrospective observational study of all patients with mNSCLC treated with ICIs, with or without combination chemotherapy, at 3 Mayo Clinic sites between 2011 and 2022. Separate analyses were conducted at 6- and 12-month intervals. Patients who discontinued ICI due to POD prior to these time points were excluded from the analysis. Results A total of 246 patients with stage IV NSCLC used ICIs. Patients were then excluded if they had experienced POD prior to 6 or 12 months, resulting in 81 and 63 patients, respectively, for each timepoint. Sixty-four patients continued treatment beyond 6 months and were found to have longer progression-free survival (PFS) compared to the 17 patients who discontinued treatment (22.8 months vs 11.8 months, P =1.1E-04), as well as a significant increase in overall survival (OS) (33.9 months vs 14.4 months, P =7.2E-08). Forty patients continued treatment beyond 12 months and had longer PFS compared to the 23 patients that discontinued treatment (27.9 months vs 14.8 months, P =1.1E-04), as well as a significant increase in OS (39.7 months vs 18.0 months, P =2.0E-07). The most common reason for ICI discontinuation was irAEs. Other common reasons for stopping ICI were non-irAEs and stable disease. At both time points, 12 patients continued or restarted ICI after experiencing an irAE, and 2 patients experienced recurrent/new grade 1–2 irAEs. More patients continued/rechallenged with ICI after experiencing an irAE in the groups that continued ICI compared to those that discontinued ICI. Conclusions Patients with mNSCLC and no POD who continued ICI beyond 6 months and 12 months, experienced significantly increased PFS and OS compared to patients who discontinued ICI, with larger increases in those who continued ICI past 12 months. Oncology providers should discuss the survival benefits of continuing ICI and offer support to overcome obstacles to continuation of treatment, if possible, particularly management of grade 1 and 2 irAEs.